An Epidemic among My People Religion, Politics, and COVID-19 in the United States - Friesen, Amanda; Djupe, Paul (Temple University Press, 2023)
The pandemic presented religion as a paradox: faith is often crucial for helping people weather life's troubles and make difficult decisions, but how can religion continue to deliver these benefits and provide societal structure without social contact? The topical volume, An Epidemic among My People explains how the COVID-19 pandemic stress tested American religious communities and created a new politics of religion centered on public health.The editors and contributorsconsider how the virus and government policy affected religion in America. Chapters examine the link between the prosperity gospel and conspiracy theories, the increased purchase of firearms by evangelicals, the politics of challenging public health orders as religious freedom claims, and the reactions of Christian nationalists, racial groups, and female clergy to the pandemic (and pandemic politics). As sharp lines were drawn between people and their governments during this uncertain time, An Epidemic among My People provides a comprehensive portrait of religion in American public life.